PERLINDUNGAN HUKUM BAGI LEMBAGA PERS MAHASISWA TERHADAP RISIKO KRIMINALISASI - Wahyudi; Dinda Safira Nayoni (Jurnal Hukum Positum, 2023)
The press is an institution that actualizes one of the points of human rights, namely freedom of association and expressing thoughts orally and in writing. The existence of the press has its function for society, based on people's sovereignty by the principles of democracy, justice, and the supremacy of law as a concreteization of press freedom. However, this is not the case for the position of the student press which is considered not to be a legal entity because it is still within the campus structure. Apart from that, in their activities, students cannot regularly carry out journalistic activities because they still have academic responsibilities as students. With these two aspects, it seems as if student press institutions do not meet the legal standards of press institutions, so the protection they should protect becomes unclear. Even though it is under the auspices of the campus, the editorial activities of the student press are independent without interference from the campus. As a result, if the news is about issues that offend the campus, criminalization of the student press is inevitable, especially in defamation and hate speech. Using the normative juridical method, by analyzing qualitatively it can be understood that the position of the student press seems to be constrained from all directions, between its status as a student and on the other hand as a press which should hold freedom and responsibility according to its function. So, the opportunity for all kinds of intimidation, such as threats, repressive actions and even banning, is not impossible for the student press. In the absence of legal protection, student press activities in carrying out the press function of disseminating information are hampered.